American Sociology and Holocaust Studies The Alleged Silence and the Creation of the Sociological Delay - Messina, Adele Valeria (Academic Studies Press, 2017)
Filled with new elements that challenge common scholarly theses, this book acquaints the reader with the "Jewish problem" of sociology and provides what this academic discipline urgently needs: a one-volume history of the Sociology of the Holocaust. The story of why and how sociologists as well as the schools of sociological thought came to confront the Holocaust has never been entirely told. The volume offers original insights on the nature of American sociology with implications for the post-Holocaust sociology development.